2013
DOI: 10.1155/2013/163964
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Compositions of Six Wild Edible Mushroom Species

Abstract: The fatty acids of six wild edible mushroom species (Boletus reticulatus, Flammulina velutipes var. velutipes, Lactarius salmonicolor, Pleurotus ostreatus, Polyporus squamosus, and Russula anthracina) collected from different regions from Anatolia were determined. The fatty acids were identified and quantified by gas chromatography and studied using fruit bodies. Fatty acid composition varied among species. The dominant fatty acid in fruit bodies of all mushrooms was cis-linoleic acid (18 : 2). Percentage of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 14 publications
(20 reference statements)
5
63
0
4
Order By: Relevance
“…Linoleic acid (omega-6 fatty acid) which is essential for human organism is the precursor of mushroom aromatic compounds, giving them their specific taste (Ribeiro et al 2007). The intake of dietary fats through food is necessary for optimal functioning and balance of fats in the organism (Ribeiro et al 2007;Ergönül et al 2013). Unsaturated fatty acids are essential for our health, having a strong beneficial effect in the prevention and management of cardiovascular diseases, triglyceride level, blood pressure etc., whereas saturated fatty acids, which are present in higher amounts in food of animal origin, are associated with increased levels of triglycerides in the blood and commonly are associated with hypertension etc.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linoleic acid (omega-6 fatty acid) which is essential for human organism is the precursor of mushroom aromatic compounds, giving them their specific taste (Ribeiro et al 2007). The intake of dietary fats through food is necessary for optimal functioning and balance of fats in the organism (Ribeiro et al 2007;Ergönül et al 2013). Unsaturated fatty acids are essential for our health, having a strong beneficial effect in the prevention and management of cardiovascular diseases, triglyceride level, blood pressure etc., whereas saturated fatty acids, which are present in higher amounts in food of animal origin, are associated with increased levels of triglycerides in the blood and commonly are associated with hypertension etc.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…In recent decades, due to the rising trend of a number of diseases (including auto-immune diseases, as well as cancer, hypertension, diabetes etc.) there is a public pressure to explore the possibilities of alternative therapeutic agents (Ergönül et al 2013). Wild-growing mushrooms accumulate a number of compounds: carbohydrates, fibers, vitamins, minerals, proteins, fats and different secondary metabolites with proven antimicrobial, antitumor, antifungal, antioxidant activity (Ribeiro et al 2007;Ergönül et al 2013;Wasser and Weiss 1999;Diyabalange et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Currently researchers are looking for natural sources of substances, which have the ability to capture free radicals, to stimulate the immune system and bring many other health benefits [6]. Oyster mushrooms (Pleurotus ostreatus) contain a large spectrum of medicinal substances [1,8,15], chemical elements, vitamins [10, 17] and nutrients [4,5]. Because of the presence of numerous nutritional components and various biologically active substances, the Oyster mushrooms have found a wide potential medicinal usage as a part of treatment and prevention of diseases induced as a result of modern lifestyle or malnutrition [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the linoleic acid is the precursor of arachidonic acid and it has a role in prostaglandins biosynthesis [8]. So far, some studies are reported on the fatty acids of mushrooms [5,[9][10][11][12][13][14]. Because of important properties of polyunsaturated fatty acids, scientific studies about mushrooms including polyunsaturated fatty acids have increased with each passing day.…”
Section: Introductionmentioning
confidence: 99%